2012
DOI: 10.1152/ajpgi.00016.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gut mucosal injury in neonates is marked by macrophage infiltration in contrast to pleomorphic infiltrates in adult: evidence from an animal model

Abstract: Necrotizing enterocolitis (NEC) is an inflammatory bowel necrosis of premature infants. In tissue samples of NEC, we identified numerous macrophages and a few neutrophils but not many lymphocytes. We hypothesized that these pathoanatomic characteristics of NEC represent a common tissue injury response of the gastrointestinal tract to a variety of insults at a specific stage of gut development. To evaluate developmental changes in mucosal inflammatory response, we used trinitrobenzene sulfonic acid (TNBS)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 56 publications
(69 reference statements)
10
118
0
Order By: Relevance
“…This corresponds to other studies showing an increased number of inflammatory monocytes in the small bowel of mice submitted to the NEC protocol as well as in human NEC samples (31,32). Therefore, it has been speculated that infiltrating monocytes/macrophages contribute to NEC through exaggerating the neonatal immune response by releasing proinflammatory cyto-and chemokines (33,34).…”
Section: Articlessupporting
confidence: 88%
“…This corresponds to other studies showing an increased number of inflammatory monocytes in the small bowel of mice submitted to the NEC protocol as well as in human NEC samples (31,32). Therefore, it has been speculated that infiltrating monocytes/macrophages contribute to NEC through exaggerating the neonatal immune response by releasing proinflammatory cyto-and chemokines (33,34).…”
Section: Articlessupporting
confidence: 88%
“…This reduction in TGF-␤ 2 expression is a unique feature of NEC and contrasts with inflammatory conditions of the gastrointestinal tract in older children/ adults such as ulcerative colitis and Crohn's disease (11,36), celiac disease (29), and shigellosis (39), which are associated with increased TGF-␤ expression. In a recent study, we showed that the inflammatory changes in NEC may be related not to specific etiological factors but may instead represent a generic tissue injury response of the developing gastrointestinal tract (35). We induced nonspecific intestinal injury in neonatal and adult mice by administering 2,4,6-trinitrobenzene sulfonic acid (TNBS); TNBS-enterocolitis increased TGF-␤ 2 expression in adult mice but inhib- ited its expression in pups (unpublished observation, MohanKumar K, Kaza N, Jagadeeswaran R, Garzon SA, Bansal A, Kurundkar AR, Namachivayam K, Remon JI, Bandepalli R, Feng X, Weitkamp J-H, Maheshwari A.).…”
Section: Discussionmentioning
confidence: 98%
“…To investigate whether enteral administration of amniotic fluid affected the inflammatory response during NEC, we used RT-qPCR to measure mRNA expression of selected inflammatory mediators associated with NEC (n ϭ 5 animals/group) (24). As shown in Fig.…”
Section: Amniotic Fluid Supplementation In Enteral Feeds Reduces Tissmentioning
confidence: 99%